Resuscitation of bacterial biofilm by sunlight: effects on different enteropathogenic bacteria - Pritha, Radia Shams; Jeba, Faria Rahman (Brac University, 2024)
This thesis submitted to the Department of Mathematics and Natural Sciences in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2022.